Case Report of Synchronous Prostate, Hepatocellular, and Rectal Carcinomas and Review of the Literature. (22nd January 2020) - Lamprou, Viktoria; Paramythiotis, Daniel; Giakoustidis, Dimitrios; Karakatsanis, Anestis; Astreinidis, Athanasios; Moysidis, Moysis; Mihalopoulos, Antonios; Finitsis, Stefanos
Abstract : Synchronous occurrence of three histopathologically distinct malignant tumors is a rare event, and there are no definitive guidelines about the optimal treatment of these patients. We report a case of synchronous prostate, hepatocellular, and rectal carcinomas and discuss our therapeutic strategy that resulted in excellent clinical results.